Helen Ward's beautiful birds - Ward, Helen, 1962-; Wood, A. J., 1960- (Honesdale, PA : Bell Books, 1991)
Ten birds are boldly illustrated, each accompanied by a simple, poetic narrative of their behavior.
"A Templar book"--P. facing t.p.
Spine title: Beautiful birds.
School Library Journal.
3.7
K-3
Keywords: Birds -- Juvenile literature; Birds; Birds; Birds